Consultation requirements and multidisciplinary approach in disability evaluations - Tecir, Umut; Cankurt Ayar, Nilay; Turla, Ahmet; Aydın, Berna (The Bulletin of Legal Medicine, 2025)
Objective: Disability assessment is one of the fundamental areas of forensic medicine practice. However, in the evaluation of traumatic injuries and their sequelae, the opinion of a single specialty is often insufficient. This study aimed to examine the frequency of consultation requirements, the specialties involved, their impact on reporting time, and the importance of a multidisciplinary approach in disability evaluations. Methods: A total of 508 cases who applied to the Department of Forensic Medicine at Ondokuz Mayıs University between January 1, 2020, and December 31, 2023, for disability assessment were retrospectively analyzed. Demographic data, presence of consultations, requested specialties, and reporting durations were recorded. Statistical analyses were performed using SPSS 21.0 software. Results: Among the cases, 331 (65.2%) were male and 177 (34.8%) were female, with a mean age of 37.1 ± 17.2 years. The most frequent admissions occurred in the 20–29 age group (28.4%). Consultations were requested in 61.8% of the cases, most commonly from the Department of Physical Medicine and Rehabilitation (71.7%) and Neurology (12.1%). Significant differences in reporting time were observed between cases without consultation and those requiring multiple-department, psychiatry, and otorhinolaryngology consultations, as well as between cases requiring Physical Medicine and Rehabilitation consultation and those requiring multiple-department consultations (p<0.05). Conclusion: The high rate of consultations in disability assessments highlights the necessity of a multidisciplinary approach to ensure accuracy and standardization in forensic reports. Establishing structured consultation algorithms and strengthening interdisciplinary collaboration are crucial for improving the quality and reliability of forensic medical evaluations.